Answer:
h(x) = x - 3
Step-by-step explanation:
To find the inverse of a function, you can switch the x and y variables.
In f(x) = x + 3, the y variables is "f(x)".
y = x + 3
Now switch the x and y.
x = y + 3
Isolate for y and replace with h(x).
x - 3 = y
y = x - 3
h(x) = x - 3
Your proof is correct and very well done
Whete are the given points, is thee a picture
The area of a triangle is A= 1/2bh. Plugging in the values you know, 30= 1/2*12*h.
Solving for h,
30= 1/2*12*h
30= 6h
h=5
The height of the triangle is 5 units.